Sources of variation in primary care clinical workflow: Implications for the design of cognitive support. (March 2014) - Militello, Laura G; Arbuckle, Nicole B; Saleem, Jason J; Patterson, Emily; Flanagan, Mindy; Haggstrom, David; Doebbeling, Bradley N
This article identifies sources of variation in clinical workflow and implications for the design and implementation of electronic clinical decision support. Sources of variation in workflow were identified via rapid ethnographic observation, focus groups, and interviews across a total of eight medical centers in both the Veterans Health Administration and academic medical centers nationally regarded as leaders in developing and using clinical decision support. Data were reviewed for types of variability within the social and technical subsystems and the external environment as described in the sociotechnical systems theory. Two researchers independently identified examples of variation and their sources, and then met with each other to discuss them until consensus was reached. Sources of variation were categorized as environmental (clinic staffing and clinic pace), social (perception of health information technology and real-time use with patients), or technical (computer access and information access). Examples of sources of variation within each of the categories are described and discussed in terms of impact on clinical workflow. As technologies are implemented, barriers to use become visible over time as users struggle to adapt workflow and work practices to accommodate new technologies. Each source of variability identified has implications for the effective design and implementation of useful health information technology. Accommodating moderate variability in workflow is anticipated to avoid brittle and inflexible workflow designs, while also avoiding unnecessary complexity for implementers and users.